Intradiaphragmatic bronchogenic cyst - Fernando Luíz Westphal; Arteiro Queiroz Menezes; Ricardo Alexandre Gonçalves Guimarães (2003)
The bronchogenic cyst is a common congenital malformation, generally located in the mediastinum; however, it can develop in other areas, such as the diaphragm. A rare case of intradiaphragmatic bronchogenic cyst is described here, discovered in a 32 year-old patient, who experienced thoracic pain and dyspnea following thoracic trauma. The pre-operative exams were compatible with left diaphragmatic hernia. The patient was submitted to a left post-lateral thoracotomy with the operative discovery of a cystic lesion enveloped by the diaphragm with mucinous content, and a partial resection of the diaphragm was performed. The histological findings of the operated portion revealed ciliated cylindrical epithelium, compatible with bronchogenic cysts. The post-operative outcome was excellent.